Exploring patients' engagement with web-based peer support for Inflammatory Bowel Disease: forums or Facebook? - Coulson, Neil S. (The British Psychological Society, 2015)
Whilst the popularity of health-related peer-to-peer web-based support shows no sign of diminishing, comparatively little is known about the factors associated with engagement in alternative web-based types of support (e.g. chat rooms, discussion forums, social networking sites). In this study, 147 patients living with Inflammatory Bowel Disease (IBD) completed an online questionnaire and described their use of either IBD forums or IBD Facebook groups along with a range of socio-demographic, disease-related and psychosocial factors. The findings revealed that over half (59 per cent) of respondents accessed forums with the remaining accessing Facebook groups. Members of Facebook groups were more likely to be younger, single and achieved a higher level of educational attainment compared with forum members but there was no difference in terms of disease-related characteristics. However, differences did exist in how they used web-based support with forum members having been members for longer, accessing them more frequently and spending longer online as well as posting more messages. Taking into account these background variables, there were no differences in terms of perceived stress, perceived social support and health-related quality of life between members of these two types of support communities.